1987
DOI: 10.1212/wnl.37.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's disease and dementia

Abstract: Norepinephrine, 3-methoxy 4-hydroxyphenylethyleneglycol and homovanillic acid levels were similar in the locus ceruleus of 13 controls and 8 parkinsonian patients with no intellectual deterioration, but were decreased in 7 demented patients. The concentration of dopamine was similarly diminished in non-demented and demented parkinsonians, and binding of 3H-desmethylimipramine and 3H-rauwolscine was not abnormal in parkinsonians. These data indicate that norepinephrine metabolism in the locus ceruleus is subnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(83 citation statements)
references
References 0 publications
3
80
0
Order By: Relevance
“…Current thinking now recognises the heterogeneity in disease pathology and that this mirrors the complexity of the non-motor symptoms also associated with the disorder (Chaudhuri et al, 2006). Indeed, beyond causing pronounced dopaminergic disturbances, the degeneration also involves the serotonergic, noradrenergic and cholinergic systems as evidenced by neuronal losses and inclusion pathology in the locus coeruleus (Cash et al, 1987;Zarow et al, 2003), dorsal raphé nuclei (Scatton et al, 1983) and the basal nucleus of Meynert (Mann and Yates, 1983) respectively. The disorder is associated with a large number of intrinsic non-motor symptoms such as visuospatial deficits, autonomic dysfunction, cognitive impairment and neuropsychiatric problems.…”
Section: Discussionmentioning
confidence: 99%
“…Current thinking now recognises the heterogeneity in disease pathology and that this mirrors the complexity of the non-motor symptoms also associated with the disorder (Chaudhuri et al, 2006). Indeed, beyond causing pronounced dopaminergic disturbances, the degeneration also involves the serotonergic, noradrenergic and cholinergic systems as evidenced by neuronal losses and inclusion pathology in the locus coeruleus (Cash et al, 1987;Zarow et al, 2003), dorsal raphé nuclei (Scatton et al, 1983) and the basal nucleus of Meynert (Mann and Yates, 1983) respectively. The disorder is associated with a large number of intrinsic non-motor symptoms such as visuospatial deficits, autonomic dysfunction, cognitive impairment and neuropsychiatric problems.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal loss in locus coeruleus (LC) and noradrenergic deficiency in the cortex were reported to be associated with dementia in PD (Cash, 1987). However, in other studies, this relationship could not be found (Paulus, 1991;Chan-Palay, 1989).…”
Section: Pathophysiology Of Cognitive Deficits and Dementia In Pdmentioning
confidence: 97%
“…Despite the focus on DA, PD is more accurately described as a multisystem disorder that features a profound albeit underappreciated loss of locus coeruleus (LC) neurons, as well as variable damage to other brain regions (4)(5)(6). Postmortem studies indicate that neuronal degeneration in the LC is comparable to that in the substantia nigra pars compacta, and that it may actually precede DA degeneration in PD (5,7,8).…”
mentioning
confidence: 99%